University–industry linkages in the UK: emerging themes and 'unanswered' questions. (1st December 2014) - Gilman, Mark; Serbanica, Cristina
Abstract : With university–industry engagement forming an integral part of the policy agenda, this paper underlines current issues and emerging themes in the dedicated literature. It utilises a comprehensive literature review, based on evidence from peer-reviewed journals/public reports published after 2005 in the UK. The paper integrates a wide range of disparate studies on university–industry knowledge transfer patterns, determinants and impacts, and offers a panorama that could be useful to inform on the variety of issues underlying knowledge transfer. Given the importance/complexity of university–industry interactions, a comprehensive study fills an existing gap. Second, due to its focus on current issues, the study opens the way to reflections and debates on critically 'unanswered' questions: how to deal with diversity/heterogeneity? How to increase quality in supply/quantity in demand for knowledge? How to increase impact on academics, universities, firms, economy and society?